2004
DOI: 10.1097/00003677-200401000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Why Rest Stimulates Bone Formation: A Hypothesis Based on Complex Adaptive Phenomenon

Abstract: Moderate exercise is an ineffective strategy to build bone mass. The authors present data demonstrating that allowing bone to rest between each load cycle transforms low- and moderate-magnitude mechanical loading into a signal that potently induces bone accretion. They hypothesize that the osteogenic nature of rest-inserted loading arises by enabling osteocytes to communicate as a small world network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…These findings further confirm the widely held belief that better osteogenic effects are observed when the exercise load is divided equally over 3 or 5 days per week than when performed once a week. It is also consistent with the recommendation of insertion of rest intervals between loading events to greatly help the amplification of the response of bone to mechanical loading [27,28]. This recommendation has been supported by several external loading studies, which found that mechanical loading protocols are more osteogenic if the load cycles are divided into several discrete bouts, separated by 3 to 8 h of rest period, than if the cycles are applied in a single uninterrupted bout in rats [21,29,30,31].…”
Section: Discussionsupporting
confidence: 81%
“…These findings further confirm the widely held belief that better osteogenic effects are observed when the exercise load is divided equally over 3 or 5 days per week than when performed once a week. It is also consistent with the recommendation of insertion of rest intervals between loading events to greatly help the amplification of the response of bone to mechanical loading [27,28]. This recommendation has been supported by several external loading studies, which found that mechanical loading protocols are more osteogenic if the load cycles are divided into several discrete bouts, separated by 3 to 8 h of rest period, than if the cycles are applied in a single uninterrupted bout in rats [21,29,30,31].…”
Section: Discussionsupporting
confidence: 81%
“…This has been described by Turner, 60 for bone cells, in accommodation to a customary mechanical loading environment, making them less responsive to routine loading signals, particularly when the loading stimulus is of low magnitude. 19,57 In this study, the increase in BMP2 levels following 14 days of stimulation represents an autocrine osteogenic growth factor response to uniaxial strain. The ERK and PI3-kinase pathways are responsible for mediating this response, which is in agreement with other studies.…”
Section: Discussionmentioning
confidence: 89%
“…Reducing m from 4.5, a value suggested for low-frequency loading, (Beaupre et al, 1990), to m ¼ 1, a value suggested for high-frequency loading (Qin et al, 1998), the strength of the 90 Hz stimulus would still have been 43% greater than the 45 Hz stimulus and m would have to drop below 0.66 before the relation reverses and the 90 Hz stimulus becomes more osteogenic. Whether a dynamically adaptive index m can be realized biologically or whether our results add to the experimental inconsistencies that cannot be explained with the daily stress stimulus hypothesis (Adams et al, 1997;Gross et al, 2004) remains to be determined.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the success of inserting rest periods into low-frequency high-magnitude loading schemes to overcome saturation (Gross et al, 2004), rest periods during extremely low-magnitude WBV do not seem to potentiate bone's response (Xie et al, 2006b), further suggesting that saturation to the number of loading cycles does not play a major role during low-level WBV. Consistent with this view, preliminary data indicate that doubling the number of loading cycles, for a given vibration frequency and acceleration amplitude, may significantly enhance bone morphology in the adolescent mouse (Xie et al, 2006a).…”
Section: Article In Pressmentioning
confidence: 99%